THE METHODICAL APPROACHES OF THE FORMATION OR WEST KAZAKHSTAN REGION’S ECOLOGICAL FRAMEWORK - Zh Zh Myrzagalieva; E V Stanis (RUDN Journal of Ecology and Life Safety, 2015)
The article describes the methodical basis of the creation of territory ecological framework (EF) in order to preserve biological diversity. The basic methodical approaches that should be based in creating of ecological framework of the territory have been singled out.They are landscape-geographical, basin and complex ones. It is offered to create the ecological framework of West Kazakhstan region (WKR) basing on present 10 specially protected natural areas. Specially protected natural areas on the territory of WKR have been represented by 3 zoological state reserves such as Kirsanovsky, Budarinsky, Zhaltyrkulsky, and by 7 local regional reserves such as biological reserve “Dubrava”, “Mirgorodsky”, “Selectsionnyi”, complex reserve “Urdinsky”, geomorphological reserve “Ak-kum”, also natural monument “Grand Ichka” mountain, monument “Sadovksoye” lake. Total area of protected areas of WKR are 188, 7 ha or 1,25% of all territory.It should use the landscape method to create EF of WKR using the remote sensing data. The using of the landscape method can consider the peculiarities of all nature complexes of specially protected natural areas, anthropogenic impact’s degree. During the design phase of EF it will be presented the cartographic patterns based on remote sensing.